INDICATIONS FOR DIAGNOSTIC LAPAROSCOPY IN VARIOUS STAGES OF TREATMENT OF PATIENTS WITH OVARIAN CANCER - A. S. Khadzhimba (Сибирский онкологический журнал)
The experience in performing laparoscopic surgery for ovarian cancer patients was analyzed. Laparoscopic surgery with biopsy is currently the optimal diagnostic technique before starting systemic treatment in patients with advanced ovarian cancer. This procedure allows not only to obtain morphological verification but also to evaluate the extent of ovarian cancer involvement and its respectability. Laparoscopy is preferred over laparotomy because of its minimally invasive nature and shorter healing time, with comparable results in terms of the surgical outcomes and oncological safety.